1996
DOI: 10.1016/0016-7061(95)00062-3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of infiltration rates under contrasting slope conditions in southeast Spain

Abstract: Infiltration is the key process in the rainfall-runoff relationship. Little is known, however, about the seasonal and spatial variability, which is important for the behaviour of the slope surface geomorphological processes.The infiltration rates for contrasting slopes in southeast Spain have been measured by means of simulated rainfall and ponding. A north-and a south-facing slope were selected to analyze effects of aspect. The results show that aspect as well as slope position and vegetation cover determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
3
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(116 citation statements)
references
References 20 publications
8
98
3
7
Order By: Relevance
“…2). Storms similar to the ones simulated have a return period of 10 years in the study area (Cerdà, 1996;Elías and Ruiz, 1977) and are those that contribute to the majority of surface runoff and soil erosion in the study area. The barley straw cover (75 g of straw per m 2 ) was applied before the rainfall experiments at doses that provided a soil cover ranging from 48 to 90% of the soil surface area, with an average value of 62.2%.…”
Section: Materials and Instrumentssupporting
confidence: 52%
See 1 more Smart Citation
“…2). Storms similar to the ones simulated have a return period of 10 years in the study area (Cerdà, 1996;Elías and Ruiz, 1977) and are those that contribute to the majority of surface runoff and soil erosion in the study area. The barley straw cover (75 g of straw per m 2 ) was applied before the rainfall experiments at doses that provided a soil cover ranging from 48 to 90% of the soil surface area, with an average value of 62.2%.…”
Section: Materials and Instrumentssupporting
confidence: 52%
“…The main reason for their high erodibility are practices that keep the soil between the vines bare during the entire year (Arnáez et al, 2007;Lasanta and Sobrón, 1988) and these bare surfaces are affected by intense storms that induce severe water erosion and runoff processes (Borga et al, 2011;Poesen and Hook 1997;Santos, 2000). Moreover, vineyards are often planted on steep-sloping soils (Arnáez et al, 2007;Wichereck, 1993) with poor nutrient and organic matter content (Cerdà, 1996;Corti et al, 2011;Novara et al, 2011Novara et al, , 2013. Changes in land use and farming practices or land abandonment have also negatively affected Mediterranean vineyards (Cerdà, 1994;Porta et al, 1994;Tarolli et al, 2014Tarolli et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…At the aim of estimating soil sorptivity, tension infiltration experiments are preferred to ponded ones to exclude the contribution of macropores that may overwhelm soil hydrophobicity (Cerdà, 1996;Ebel et al, 2012;Nyman et al, 2010). Miniaturized tension infiltrometers were proposed to determine SWR (Hallett et al, 2001;Vogelmann et al, 2013), but their use is confined to the aggregate scale and, for field use, standard infiltrometers are more suited.…”
Section: Introductionmentioning
confidence: 99%
“…For plots 1, 2 and 3, a single rainfall experiment was carried out, while for plot 4, four rainfall experiments were carried out during four consecutive days, and are referred to in the text as 4A, 4B, 4C and 4D. Storms similar to the ones simulated have a return period of 10 years in the study area (Cerdà, 1996;Prosdocimi et al, 2016b). The rainfall simulator used was the one described by Cerdà et al (1997) because it revealed to be effective in rugged terrain conditions proving to give good results in semi-arid environments.…”
Section: Rainfall Simulationmentioning
confidence: 99%
“…As the nozzle was kept at about 2 m height over a plane surface, the 0.25 m 2 plots were established at the centre of the 1 m 2 sprinkling area, to avoid border interference. Readers are referred to Cerdà et al (1997) and Iserloh et al (2013) for a further description of the rainfall simulator used and Cerdà (1996Cerdà ( , 1997 for more information about the distribution of rainfall parameters. Surface runoff from the plots were collected and measured at 1-min intervals during each simulated rainfall event.…”
Section: Rainfall Simulationmentioning
confidence: 99%